Symbolic Visualization of the Cowong Banyumas Doll using the Iconology-Iconography Theory of Erwin Panofsky - Nofrizaldi, Nofrizaldi (Budapest International Research and Critics University, 2022)
This research is qualitative in nature using an art history method approach to understand the symbolic visualization of the Cowong Banyumas doll using the iconology-iconography theory of Erwin Panofsky. The methods used are (1) topic selection (2) collection of written, artefact, and oral sources, (3) verification/critique of sources (4) interpretation in the form of analysis and synthesis, (5) writing of research results. The result of the research is a pre-iconographic description related to the textual aspects of the Cowong doll which is a work of art made from materials that exist in the daily environment of the Banyumas people, made with a form stylization technique with a decorative style. In the iconographic analysis related to the theme and concept of the Cowong doll, it is concluded that the Cowong doll is a form of communication media for life problems due to a long drought (prey for famine) so that it has an impact on the lives of the agrarian Banyumas people. In the iconological interpretation related to symbolic value, the Cowong doll is a medium created through the spirit of art with the embodiment of feelings, emotions, and actions to convey communication to the Almighty through objects from nature. In the Cowong doll, there are several interconnected systems namely between humans, ancestral culture, nature, and religion. This can be categorized as syncretism, which is something that is achieved from a process to process, unite, combine and harmonize several existing systems.